Effectof contextual significance in understanding text - Abd Allah, Abd ALateef Sobhe (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aims at shedding light on the theory that is truly one of the most important linguistic theories that influenced and influenced the Arabic language lesson after the fifties of the twentieth century. The study of this theory has been used to reveal the arguments of our Arab scientists concerned with the social aspect of the language and to pay greater attention to the personality of the speaker Psychological, social and cultural, and their impact on the production of the speech event. And based on the famous saying "for each article", and its importance in determining the intended meaning of the speech event, which combines the production of a series of interrelated relations, from the speaker and through the address and understanding of the language message, and to the conditions surrounding the speech event, , Which in turn leads to a real understanding of the text using other contexts of the text . The discussion focused on the distinction between speech and speech, and the views of the ancients and the modern linguists in it, indicating the value of the lexicon in the text, and the role of suggestive in the interpretation of meaning within the linguistic context, which in turn leads to the analysis of the lexicon word in terms of contextual significance. As well as the relationship between the speaker and the interlocutor, the relationship between the time and place, and the role of speech impediments in understanding the text, and ended the research concluded The main findings from this study include proven sources and references .